Variation for aggressiveness within and between lineages of Xanthomonas oryzae pv. oryzae - Mundt, C.C.; Nieva, L.P.; Vera Cruz, C.M. (Wiley, 2002)
Isolates of Xanthomonas oryzae pv. oryzae (causal agent of bacterial blight of rice) from the Philippines representing two phylogenetic lineages, and five haplotypes within those two lineages, were evaluated for aggressiveness in two glasshouse trials. Aggressiveness was determined by clip‐inoculating leaves of a rice cultivar lacking known, effective major genes for resistance and measuring the lengths of resulting lesions. Variance components analysis indicated that 55 and 46% of the lesion length variation were genetic in origin for the first and second trials, respectively. Variation of lesion length among isolates within haplotypes was highly significant in both trials (P = 0·002 and 0·027), but the effects of lineage and haplotype within lineage were not (P = 0·08 and 0·30 for lineage and P= 0·23 and 0·07 for haplotype). These results suggest that substantial heritable variation for aggressiveness exists within Philippine populations of X. oryzae pv. oryzae. This variation appears to be more prevalent within than among known phylogenetic groups, although mean differences among phylogenetic groups may still be of significant biological importance.